Taquicardia supraventricular por reentrada AV ortodrómica en el síndrome de Wolff Parkinson White - Mestre-Sequeda, Epitafio Rafael (2023)
A 40-year-old man with a history of obesity and cannabis use consulted for an episode of sudden onset palpitations and chest pain. The electrocardiogram showed a preexcitation pattern compatible with WPW syndrome. Catheter ablation was indicated. The electrophysiological study documented a left posterolateral accessory pathway at the level of the posterolateral mitral annulus, with anterograde and retrograde conduction; however, the catheter could not be positioned at the site, with poor contact, so modulation of the endocardial arrhythmic substrate was considered with ambulatory three-dimensional electroanatomic mapping system.